A comparative study of strategies for identifying credible sources of mental health information online: Can clinical services deliver a youth‐specific internet prescription?. Issue 6 (2nd September 2021) - Flint, Molly; Inglis, Georgina; Hill, Annabel; Mair, Mabli; Hatrick, Sophie; Tacchi, Mary Jane; Scott, Jan
Abstract: Background: Adolescents and young adults undertake internet searches before and after attending mental health consultations, but they express concerns about how they can identify reliable online mental health information (OMHI). This action research project examines how clinicians might direct young people towards credible OMHI by analysing which search strategies are most helpful for developing an 'internet prescription' targeted at a youth audience. Methods: Recently qualified doctors undertook searches for OMHI about the diagnosis and treatment of seven mental health conditions. Rankings of websites in search results were compared with reliability and quality ratings derived from established evaluation instruments [the Brief DISCERN and the 12‐item Health on the Net (HoN) tool]. Results: Of 140 websites identified through seven Google searches, only 15% of those evaluated were categorized as high quality. About 17% of websites were selling a treatment or service and about 25% were regarded as untrustworthy. Also, higher rankings in the search results were not indicative of better quality OMHI (Wilcoxon signed rank test: Z  = −5.28; p  < .001). Although the HoN and DISCERN tools provided useful insights into the credibility of OMHI, investigators did not think either instrument could be recommended for independent use by youth. Conclusions: Our findings suggest that clinical services should take responsibility for identifying a range of credible sources of OMHI. The next step in translating the research strategy into clinical practice involves collaboration with young people to select those platforms most orientated to their needs and to develop rating instruments that enable youth to evaluate OMHI.